Windows Server Hybrid Administrator Associate (AZ-800) Cert Prep: 1 Deploy and Manage Hybrid Active Directory Services. - Rahman, Seema (linkedin.com, 2022)
Learn how to prepare for the Deploy and Manage Hybrid Active Directory Services domain of the Microsoft AZ-800 certification exam.